Amino-ether macrocycle that forms CuII templated threaded heteroleptic complexes: a detailed selectivity, structural and theoretical investigations1. Issue 34 (14th September 2015) - Santra, Saikat; Mukherjee, Sandip; Bej, Somnath; Saha, Subrata; Ghosh, Pradyut
<x xml:space="preserve">Abstract</x> Self-sorting behavior of a newly synthesized macrocycle with divalent metal ions and aromatic ligands via pseudorotaxane formation has been described.